Vaginal rejuvenation: From scalpel to wands - Sejal A. Desai, MD; George Kroumpouzos, MD, PhD; Neil Sadick, MD (Wolters Kluwer, 2019)
Vaginal rejuvenation procedures are increasing in popularity in terms of types of treatment offered, number of patients undergoing them, clinical studies, and in the controversy surrounding them. Both non-invasive and invasive solutions are being developed by pharmaceutical and technological companies. Radiofrequency devices and lasers are spearheading the energy-based device space, and fillers and platelet-rich plasma are used to address several concerns surrounding vaginal health. In this review, an overview of the growing field of vaginal rejuvenation is presented, as well as the authors' personal view and analysis of this clinical space.